Occurrence of Headache with and without Pillow Cushion in Supine Position after Spinal Anesthesia - Maharjan, Devendra (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study was designed to define the role of position in the occurrence of postdural puncture headache (PDPH) after spinal anesthesia.Methods: This is a comparative study of 69 patients in each group with pillow cushion and without during spinal anesthesia in supine position for the patients scheduled for low abdominal and pelvic surgeries.Results: Patients in both groups experienced headache (but not PDPH) after surgery with slightly higher (n=13, 18.84%) rate in strict supine position than with head rest using a pillow cushion (n=11, 15.94%). This was not statistically significant (p=0.65).Conclusions: Supine position with a pillow cushion in the immediate post-spinal period caused a non-significant decrease in the incidence of headache and a significant increase in comfort. This study could not conclude whether a pillow cushion affects the occurrence of PDPH as there were no cases of PDPH in either group.